STUDY ON CATHFISH (Clarias batrachus) BEHAVIOR IN THE CAPTURE PROCESS BY PVC TRAP - Ridho Romola S; Nofrizal '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Purpose of this study is to test effectiveness of PVC and conventional trap to catch C. Batrachus as main fishing target. C. Batrachus behavior on the fishing capture process by PVC and conventional trap were observed in the tank 9 x 1 x 1.5 m in dimension and under video camera (JVC, HDD Evero 35 X optical zoom) recording. The result show that, the PVC trap was most effective to catch, which the total fishing catches were 21 individuals. The average of duration time was spent between 1.53 – 183.15 minutes for each individual to enter in to PVC trap during observation. While, the conventional trap was caught 8 individuals, which was reqiured time between 3.23 – 424.12 minutes. The capture process of C. Batrachus was varied, they were surrounded in front of tunnel of the trap before go toinside it as well as another individual directly go to inside the trap. The effectiveness of capture process was influenced by short time the C. Batrachus enter to the trap, which C. Batrachus was required times 1.53 minutes each individuals in average for PVC trap and 3.23 minutes for conventional trap. The C. Batrachus behavior related to the fishing capture process was discussed in this paper.Key words: Cathfish (C. batrachus), Conventional Trap, PVC Trap, Trap, Tank